ANALISIS KRITIS IMPLEMENTASI TAKLID DALAM BERAGAMA DALAM TINJAUAN USHUL FIQH EMPAT MAZHAB DAN PENGARUHNYA TERHADAP NILAI-NILAI KEBANGSAAN NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) - Alfa Syahriar; Ahmad Fauzan Mubarok (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
This study was conducted to discuss the concept of taklid in the religiousactivity in the perspective of Ushul Fiqh in four madhhab, with theconsideration that at the level of implementation, the concept was stillproblematic, so the consequence  was cause someone can easily fall into thetrap of fanaticism that leads to radicalism, as a result of the weakening ofcritical reason-related the quality of the received religious information-and thebarrenness of the creative power-related to the application of Islamicteachings in the reality of national and state life.